„Просто наступила зима” – повторительный урок для раздела 1 (времена года) учебника „Вот и мы 2” - Wiatr-Kmieciak, Małgorzata (Studia Rossica Posnaniensia, 2015)
Learning through play is a well-known part of a human being’s social and emotional development. Children learn very important social skills through games and role-playing. Teaching through play is also a widely recognized method of language acquisition. When playing, students learn faster and are more motivated to revise material, because they do not usually see play as a boring part of an educational program or as something they have to do, but as a “fun” part of a lesson. In this paper, the author presents certain ideas for revising the “seasons of the year” chapter of the student’s book Вот и мы 2 in a less formal way. Popular quizzes such as “hangman” or “mind maps” can be easily transformed into an educational game that will turn an ordinary revision lesson into a more creative and effective form of learning.